TELEVISION VIEWING IN THE KENYAN EDUCATION SYSTEM - NGUGI, KIARIE CAROLINE (IJRDO- Journal of Educational Research, 2018)
This paper examines the concept of knowledge in Television viewing in Kenyan schools.Television viewing in schools has its attributes that are relevant to the education system.The study explores the effects of unmonitored Television viewing in High Schools in Kenya.